Biochemical and structural characterization of chlorite dismutase enzyme from Pseudomonas aeruginosa - Nokas, Dimitrios V.; Panagiotopoulou, Eleni K.; Kapogiannatos, Antonios I.; Premetis, Georgios E.; Labrou, Nikolaos E.; Efthimiadou, Eleni K.; Papageorgiou, Anastassios C.; Chronopoulou, Evangelia G. (Wiley, 2026)
Industrialization and urbanization have caused serious contamination of water bodies, and the removal of chemical contaminants has become a major challenge. Chlorite is a harmful anthropogenic compound with a serious environmental impact and has been detected in groundwater, drinking water, and soil. Enzymes are considered sustainable tools for bioremediation, with chlorite dismutase (Cld) being a notable example. This enzyme has unique properties owing to the rare dioxygen bond formation that it catalyzes. In the present study, we report the cloning, biochemical, and structural characterization of the dimeric Cld from Pseudomonas aeruginosa (PaCld). PaCld is a heme b oxidoreductase that can decompose chlorite (ClO−2 or OClO-) into harmless chloride (Cl-) and dioxygen (O2) with high turnover rates. The structure of PaCld was determined at atomic (0.99 Å) resolution using X-ray crystallography. Additionally, steady-state kinetics and stability studies provided valuable insights into the catalytic mechanism of dimeric Clds. Apart from chlorite bioremediation of water, Clds can also be used in biomedical and synthetic biology as well as in enzymatic cascades with O2-utilizing enzymes.
Keywords: Cld structure; Cld thermostability; chlorite degradation; chlorite dismutase; heme b‐containing oxidoreductases.